Agricultural adaptation and mitigation review: Evidence for synergies and tradeoffs - Barbieri, Lindsay (2018)
Presentation by Lindsay Barbieri, University of Vermont International conference on agricultural emissions and food security: Connecting research to policy and practice 10-13 September 2018 Berlin, Germany